The role of IPO proceeds disclosure on survival of public listed companies in Malaysia / Siti Sarah Alyasa Gan - Alyasa Gan, Siti Sarah (2022)
This study examines the relationship between the role of IPO proceeds and survival period of companies in the Malaysian market. Studies on the survival period of companies are crucial, particularly in Malaysia, as it goes consistent with Bursa Malaysia’s initiatives in establishing frameworks (Practice Notes and Guidance Notes) to elongate companies’ survival post-IPO. While the performance of the Main market is referred to as the benchmark index of the Malaysian stock market performance, the observation on the declining number of total listed companies in the Malaysian market, especially among the Main Market participants portrays the Malaysian stock market’s underperformance. This study also observes that the shortest survival period for inactive companies listed from 2000 to 2020 in the Malaysian market is less than 12 months. Consequently, this may discourage investors from making potential investments in the market. Responding to the urge of companies facing difficulties to survive longer post-IPO, this study examines the determinants of companies’ survival period focusing on each category (growth opportunities, debt repayment and working capital) of the proportion of IPO proceeds and the time frame of proceeds utilization. Despite the information of IPO proceeds to be disclosed at the earliest stage of an IPO, it has a great potential to act as a predictive role to reflect the companies’ commitment in their future directions and signal their survival period. Therefore, this study attempts to achieve the following objectives: 1) to investigate the relationship between the proportion of IPO proceeds for growth opportunities and companies’ survival period; 2) to investigate the relationship between the proportion of IPO proceeds for debt repayment and companies’ survival period; 3) to investigate the relationship between the proportion of IPO proceeds for working capital and companies’ survival period; 4) to investigate the relationship between the time frame to utilize growth opportunities and companies’ survival period; 5) to investigate the relationship between the time frame to utilize debt repayment and companies’ survival period and; 6) to investigate the relationship between the time frame to utilize working capital and companies’ survival period. This study examines 423 IPO companies in Malaysia from 2000 to 2014 and employs the Accelerated Failure Time (AFT) model. This study finds evidence that the proportion of IPO proceeds and the time frame to utilize the IPO proceeds fully can reflect the commitment of management in achieving their objectives and signal the longevity of companies’ survival post-IPO. This study found debt repayment as the critical driver of companies’ survival period. A higher IPO proceeds utilized for growth opportunities and debt repayment will lead to a shorter survival period post-IPO. In contrast, a longer time frame utilizing the debt repayment leads to a longer survival period. The results support that the information disclosure requirements taken by the Securities Commission Malaysia (SCM) have led to an efficient conduit for mobilizing IPO proceeds in promoting a more transparent stock market and, therefore, protecting investors’ interests and improve the survival period of companies. The results provide empirical evidence that Malaysian listed companies’ survival period is explainable by the IPO proceeds information, extending the limited literature of studies on companies’ survival period, specifically in the Malaysian market.